2013
DOI: 10.1080/02705060.2012.708673
|View full text |Cite
|
Sign up to set email alerts
|

Inter-annual patterns in the stability and persistence of stream macroinvertebrate communities: relationship with water physicochemical parameters

Abstract: The relationships between temporal patterns of macroinvertebrate community and water physicochemical parameters were investigated in the Xiangxi River, which is the largest tributary to the Three Gorges Reservoir (TGR) in Hubei province, China. The construction of the TGR has strongly impacted the Xiangxi River watershed, but inter-annual patterns in stream macroinvertebrate communities have not been examined. We sampled water and macroinvertebrates monthly from 2004 to 2006. We assessed the persistence (simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…We did not find interannual variations in the measured hydrologic and water quality parameters to be predictors of the observed changes in the bioassessment metrics. The lack of a relationship between the measured environmental parameters and community composition is not consistent with past studies, which have found changes in flow conditions and water chemistry to impact temporal variation in benthic invertebrate communities (e.g., [19,20,47]). A possible explanation for the difference between our study and past studies is that the widespread and long-term exposure the study streams have had to anthropogenic disturbance has removed all sensitive taxa from the regional species pool and thus the measured parameters did not impart significant stress on these remaining tolerant taxa.…”
Section: Temporal Variations In Benthic Macroinvertebrate Communitiescontrasting
confidence: 55%
“…We did not find interannual variations in the measured hydrologic and water quality parameters to be predictors of the observed changes in the bioassessment metrics. The lack of a relationship between the measured environmental parameters and community composition is not consistent with past studies, which have found changes in flow conditions and water chemistry to impact temporal variation in benthic invertebrate communities (e.g., [19,20,47]). A possible explanation for the difference between our study and past studies is that the widespread and long-term exposure the study streams have had to anthropogenic disturbance has removed all sensitive taxa from the regional species pool and thus the measured parameters did not impart significant stress on these remaining tolerant taxa.…”
Section: Temporal Variations In Benthic Macroinvertebrate Communitiescontrasting
confidence: 55%
“…Environments with a high frequency of hydrological disturbance (torrential rivers) or prolonged extreme flows (floods and droughts), however, could encourage local communities that are regulated by regional environmental variables. In fact, changes to species' relative abundance and persistence (presence or absence) may be caused by hydrologically extreme disturbances (Wang et al ., ). These disturbances would act as selective forces on species, alternately selecting those best adapted to a given condition.…”
Section: Introductionmentioning
confidence: 97%
“…Ríos-Touma et al (2009) suggest that although allochthonous organic matter (litter) inputs (used as shelter or food) depend on growing or transitional periods, their retention depends not only on the magnitude and variability of the discharge but also on the geomorphology of the river. Hydrological disturbances are events that affect assemblages according to the afore mentioned habitat characteristics, which cause changes to relative taxonomic abundance and persistence (presence/absence), selectively decreasing certain taxa (Hendricks, 1995, Swanson et al, 1998Lake, 2000, Wang et al, 2013. Likewise, ecosystem function can be altered, so that changes in the functional feeding groups (FFG) or life habit composition may also be used as indicators of ecosystem change and recovery after disturbances (Ramírez and Gutierrez-Fonseca, 2014).…”
Section: Introductionmentioning
confidence: 99%